Emotional labour and the ‘never-ending shift’- narratives of working mothers during the Covid-19 pandemic - Khan, Arshima (My University, 2022)
The Covid-19 pandemic in 2020 has emphasized the simultaneous necessity and invisibility of care work and emotional labour undertaken by working mothers, disproportionately increasing their domestic, childcare and employment responsibilities. It highlighted the centrality of relational care ethics, revealing the indispensability of unacknowledged care work to the economy and human survival.. This study aimed to explore narratives of 10 working mothers about their experiences of the extended lockdown from March to July 2020, to observe aspects of emotional labour and the never-ending shift undertaken by them. This study employed a cross-sectional qualitative research design, using purposive sampling and narrative methodology through a feminist, critical and Foucauldian narrative theoretical framework. Experiences and perceptions of participants were explored through a critical feminist lens to examine discursive complexities that emerged through semi-structured interviews. Narrative analysis demonstrated the socioeconomic intersections of emotional labour performed by participants, as well as the active centring of care work within their lives. It also revealed the complexities of choices that participants face, showing the concurrent resignation towards and ownership of the challenges placed upon them as mothers in a patriarchal society. A Foucauldian and critical reading of narrative themes exhibited the various ways that participants subvert and reproduce patriarchal matrices in their daily lives, as well as the idealisation and apotheosis of motherhood that occurs in society. This study emphasises the inherent economic and societal value of care work and defines it beyond capitalist narratives of valuable labour. Future research can expand further upon the racial and socioeconomic dynamics of emotional labour and care work undertaken by women.
A research report submitted in partial fulfilment of the requirements for the degree Master of Arts in Social and Psychology Research Psychology to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, 2022